PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN PELUANG USAHA TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS JAMBI ANGKATAN 2023 - Amanda, Fauziah Riyan; Fachruddiansyah Muslim; Fadilla Ulfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the phenomenon of the still high unemployment rate and limited job opportunities, including for college graduates. It is hoped that universities will be able to produce graduates who are not only oriented towards being job seekers, but also have the interest and ability to create jobs through entrepreneurial activities. Therefore, this study aims to analyze the influence of entrepreneurship education on students' interest in entrepreneurship, business opportunities on students' interest in entrepreneurship, and entrepreneurship education and business opportunities simultaneously on the interest in entrepreneurship of students of Economics Education, Jambi University, class of 2023. The research method used is quantitative associative with the population and sample of economics education students from the 2023 intake. Furthermore, data analysis was carried out with the help of SPSS through descriptive analysis tests, analysis prerequisite tests, classical assumption tests, multiple linear regression analysis tests, hypothesis tests.